First Order Certainty Equivalence - Malinvaud, E. (Econometrica, 1969)
Abstract : Given any problem of decision under risk to which the expected utility hypothesis applies, one may associate to it first a riskless problem in which random disturbances are replaced by their expected values, and second a class of intermediate risky problems with decreasing degrees of uncertainty. In this class the optimal decision depends in principle on the degree of uncertainty but turns out to be independent of it, to the first order of approximation, in the neighborhood of the riskless problem. The first-order certainty equivalence explains why it is so difficult to characterize the situations in which an increase in the degree of uncertainty requires a decrease in the allocation of resources to the risky projects. (Author)